Analisis SWOT agribisnis kapuk randu di desa Sekarmojo kecamatan Purwosari kabupaten Pasuruan - Novi Itsna Hidayati (Fakultas Pertanian Universitas Yudharta Pasuruan, 2020)
Cottonwood is one of the local commodities that have been cultivated by the community. This is interesting in the selection of kapok as a symbol of Pasuruan Regency which shows one of the main examples and economic support for the community. Kapok Pasuruan production contributed 29.8% of the total production of East Java, namely 25.288 tons. The increasing presence of synthetic fibers drives demand for fiber from kapok cottonwood so farmers are reluctant to increase cottonwood trees more intensively and do not need to cut down to replace other commodities. This if left unchecked will further decrease, kapok production and extinction can occur. This study aims to identified internal and external factors in kapok agribusiness and develop alternative development strategies using the SWOT method. The results showed that several strategies S-O, W-O, S-T and W-T.